Efficient frequency reuse scheme for multi-cell OFDMA systems - Najjar, A.; Hamdi, N.; Bouallegue, A. (2009 IEEE Symposium on Computers and Communications, 2009)
In this paper, we propose an efficient frequency reuse scheme for the downlink environment of multi-cell orthogonal frequency division multiplexing access (OFDMA) systems with 19-cell-structure, that provides an efficiency reduce of the co-channel interference (CCI) at the cell-edge region. It divides each cell into two regions: central region and edge region. The frequency reuse factor (FRF) is 1 in the central region and 3 in the edge region. The main contribution of this paper is to provide an optimal dimension of regions based on the maximization of the average to variance ratio of the signal to interference plus noise ratio (SINR) at mobile station receiver. Two optimization schemes are considered for the switching between central and edge regions: the first scheme is based on the distance between user and the serving base station and the second scheme is based on the received SINR level. A selection of simulation results are used to show the performance of the proposed scheme.